Assessment of some Immunological and biochemical parameters in diabetic type 2 patients suffered of Covid-19 - Rabab Khuder Rehan; Firas Faris Rija (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
COVID-19 caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has threatened every civilian as a global pandemic. The immune system poses the critical interactive chain between the human body and the virus. The current study aimed to assessment whether comorbidity with type 2 diabetes (T2D) affects the immunological response in COVID-19 patients. This case-control study (comparative) was carried out in Baghdad Al-karkh hospitals/ isolation units for Patients covid- 19, which included 90 subjects from November 2021 to the end of April 2022, as of which 30 participants were with T2D patients, 30 were T2D patients suffer of covid-19, with positive RTPCR for covid-19 and the remaining 30 were nondiabetic (NDM) of aged (50-85) years. To study concentrations of Interleukin 6( IL-6), Interleukin 2 Receptor Beta (IL-2R β), Procalcitonin (PCT), Ferritin, D-dimer, HbA1c, blood urea(BU), and serum creatinine . The current study showed a significant increase in IL-6 (362.4±60.01pg/ml), IL-2R β (8.8±2.7%), PCT (205±25.7mg/dl), Ferritin(), D-dimer(), HbA1c(), blood urea(58±12.7mg/dl), and serum creatinine (1.1±0.2mg/dl) in T2D with COVID-19 patients compared to the control group ( 222.8±30.7pg/ml, 4.6±1.3%, 99±15.1mg/dl, 35±9.6mg/dl, 0.65±0.03mg/dl respectively, at the probability value (P˂0.05). The COVID-19 patients comorbid with T2D demonstrated distinguishable immunological parameters, which represented clinical relevancies with the predisposed disease severity in T2D.